2010
DOI: 10.1586/era.10.86
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and individualized therapy of neoplastic meningitis

Abstract: Neoplastic meningitis is a diffuse dissemination of tumor cells into the cerebrospinal fluid (CSF) and/or leptomeninges. It occurs in approximately 5-10% of malignant diseases, most often in breast cancer, lung cancer, melanoma or B-cell lymphoma. Symptoms of neoplastic meningitis are head or back pain, cranial nerve palsies, diffuse radicular symptoms or psychiatric disturbances. MRI shows nodular contrast enhancement lining CSF spaces. Positive CSF cytology requires optimal sampling and processing. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…In this palliative care setting, invasive or poorly tolerated and painful interventions should be avoided. Traditionally, intrathecal chemotherapy of NM consists of 2-3 applications per week, either by lumbar puncture or via an Ommaya reservoir [14]. Against this background, the intrathecal liposomal cytarabine formulation seems to be a valuable and comfortable treatment option, as the reduced frequency of administration represents an important advantage.…”
Section: Discussionmentioning
confidence: 99%
“…In this palliative care setting, invasive or poorly tolerated and painful interventions should be avoided. Traditionally, intrathecal chemotherapy of NM consists of 2-3 applications per week, either by lumbar puncture or via an Ommaya reservoir [14]. Against this background, the intrathecal liposomal cytarabine formulation seems to be a valuable and comfortable treatment option, as the reduced frequency of administration represents an important advantage.…”
Section: Discussionmentioning
confidence: 99%
“…62 Novel assays are being tested that may enhance the early identification of malignant cells in CSF. [63][64][65] Until then, the diagnosis is generally made after the onset of neurological manifestations, which have a rapidly fatal course for many patients. 5 When symptoms appear, most tumors have widely disseminated throughout the meninges.…”
Section: Lumbar Puncturementioning
confidence: 99%
“…Glial fibrillary acidic protein assessed by immunohistochemistry in CSF may facilitate the identification of malignant glial cells. 1,[63][64][65]97 Several studies have demonstrated that the sensitivity of flow cytometry is several-fold higher than that of cytology for detecting CSF leukemia or lym-phoma. 98,99 Flow cytometry allows for the early detection of neoplastic meningitis before the onset of clinical symptoms and CSF pleocytosis; therefore, its use may enable more effective treatment.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…
Treatment options include whole-brain irradiation, systemic chemotherapy, and intrathecal chemotherapy such as methotrexate [2]. Despite these measures, the prognosis is poor with a median survival of 2-3 months, and focal neurologic dysfunctions do not improve in most cases [1].
…”
mentioning
confidence: 99%